Weekday-weekend patterns of physical activity and screen time in parents and their pre-schoolers - Sigmundová, Dagmar (BMC Public Health, 2016)
BACKGROUND: This study focuses on the comparison of weekday/weekend parent-child behavioural patterns (step count (SC) and screen time (ST)) and answers the question of whether achieving the recommendations for daily SC (10,000) in parents also helps their preschool children achieve the recommended daily SC (11,500). METHODS: The participants (278 parents aged 30–45 and their 194 children aged 4–7) were randomly recruited from 10 Czech public kindergartens. The participants recorded SC (pedometer Yamax Digiwalker SW-200) and ST duration (proxy-report) for seven consecutive days (≥8 h/day) during September–October 2014 and April–May 2015. Differences between weekdays/weekends SC or ST were tested using a paired t-test. The odds of achieving the recommended daily SC for children were estimated using general logistic regression separately for weekdays and weekends. RESULTS: Only the mothers were found to have a significantly lower SC at weekends than on weekdays. All of the participants showed significantly more ST at weekends than on weekdays (daughters: 78.6 vs. 45.7 min/day, p < 0.001; sons: 78.8 vs. 55.8 min/day; mothers: 93.0 vs. 68.3 min/day; and fathers: 116.6 vs. 87.5 min/day). Daughters and sons were significantly more likely to achieve daily SC recommendation if a) the SC on weekdays during the daily routine in kindergarten exceeded the median of kindergarten SC or b) at weekends if their mother (OR: 9.67, 95 % CI: 3.57–26.23) exceeded 10,000 steps a day. CONCLUSIONS: Especially at weekends, preschoolers have higher odds of meeting the recommended 11,500 steps per day when their mother reaches 10,000 steps per day and this is independent of the amount of parents’ ST. Moreover, physical activity in kindergarten helps preschool children meet the 11,500 recommended steps per day on weekdays. Therefore, interventions to promote physical activity in preschoolers should focus on kindergartens and encourage involvement of their families.